(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
Polyurethane foams were fabricated with different percentages of nano titanium dioxide (TiO2) and sizing by the unsaturated polyester. In these samples, the (TiO2) nanoparticles were inserted to polyurethane foams as filler with different percentages (1%, 3%, 5% and 7wt %) to study the effect of UV radiation and (TiO2) nanoparticles on some of mechanical properties, such as (impact resistance and bending strength) as well as the chemical resistance in salt media. Results showed the impact resistance increased with increasing of the (TiO2) nanoparticles weight percentage until 3wt%. Moreover, the bending strength increased with rising in weight percentages of (TiO2) nanoparticles until 5wt%. The optimum sample of chemical resistance was 5wt% of (TiO2) nanoparticle. Finally, the UV radiation leads to decrease of the mechanical properties. Additionally, chemical resistance was decreased with UV radiation exposure. Sample with 5wt% has the best and lowest of weight loss than other samples.